Lack of replication for the myosin‐18B association with mathematical ability in independent cohorts. (1st April 2015) - Pettigrew, K. A.; Fajutrao Valles, S. F.; Moll, K.; Northstone, K.; Ring, S.; Pennell, C.; Wang, C.; Leavett, R.; Hayiou‐Thomas, M. E.; Thompson, P.; Simpson, N. H.; Fisher, S. E.; et al.
Abstract: Twin studies indicate that dyscalculia (or mathematical disability) is caused partly by a genetic component, which is yet to be understood at the molecular level. Recently, a coding variant (rs133885) in the myosin‐18B gene was shown to be associated with mathematical abilities with a specific effect among children with dyslexia. This association represents one of the most significant genetic associations reported to date for mathematical abilities and the only one reaching genome‐wide statistical significance. We conducted a replication study in different cohorts to assess the effect of rs133885 maths‐related measures. The study was conducted primarily using the Avon Longitudinal Study of Parents and Children (ALSPAC), ( N = 3819). We tested additional cohorts including the York Cohort, the Specific Language Impairment Consortium (SLIC) cohort and the Raine Cohort, and stratified them for a definition of dyslexia whenever possible. We did not observe any associations between rs133885 in myosin‐18B and mathematical abilities among individuals with dyslexia or in the general population. Our results suggest that the myosin‐18B variant is unlikely to be a main factor contributing to mathematical abilities. Abstract : We could not replicate the association of the myosin‐18B gene with mathematical ability.